Branding Strategy for An Nur II Al-Murtadlo as a Tourism Islamic Boarding School through Digital Public Relations - Fitri, Alifa Nur; Lailiyah, Nuriyatul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Islamic boarding schools are Islamic educational institutions that apply traditional learning methods such as bandongan and sorogan. The learning implemented by Islamic boarding schools has now evolved following existing developments, a shift from the traditional learning system to learning in the digital era, this has an impact on the branding strategy applied by Islamic boarding schools to the general public. The PESO model analysis at the An Nur 2 Islamic Boarding School is used to look at Islamic boarding school branding through the media, especially owned media. This article discusses the influence of the digitalization of the An Nur 2 Islamic boarding school on the branding strategy and optimization of Islamic boarding school learning in the era of digitalization. This qualitative research uses a descriptive approach, observation and online interviews as supporting data. The results of the research explain that the percentage of digitalization strength in an Islamic boarding school can have a very significant effect on strengthening the Islamic boarding school's credibility as a branding strategy and influence the success of existing learning systems and methods in Islamic boarding schools. Thus, the existence of Islamic boarding schools known as traditional Islamic education institutions can develop. both with digitalization and playing an important role in social control and branding of Islamic boarding school institutions through the media, especially, in the midst of the crisis of decreasing credibility of Islamic boarding schools in front of the general public.